Toxic epidermal necrolysis induced by moxifloxacin and exacerbated by clindamycin in an elderly patient: A case report - Yongguang Wang; Yongguang Wang; Qizheng Guo; Qizheng Guo; Zhenyang Li; Zhenyang Li; Guifen Gan; Chun Pan (Frontiers in Medicine)
Toxic Epidermal Necrolysis (TEN) is a severe skin-mucosal reaction induced by medications, commonly characterized by blister formation and widespread epidermal detachment. Typical causative agents include allopurinol, antibiotics, anticonvulsants, and non-steroidal anti-inflammatory drugs (NSAIDs), with trimethoprim/sulfamethoxazole and penicillin being the most frequently implicated among antibiotics. However, lincosamide antibiotics as the cause of aggravation are rarely reported in clinical settings. This case report presents a patient with TEN induced by quinolone antibiotics, who experienced rapid progression of the condition after combining with lincomycin antibiotics. Clinical remission was achieved through a combination of corticosteroids, intravenous immunoglobulin, and plasma exchange therapy. This report aims to enhance clinicians’ understanding of TEN by providing a detailed case presentation and discussion.